Mythology in literary culture - Willgoos, Robert; Clearvue/eav (Chicago, Ill. : Clearvue/eav, 2000)
Explores different mythological archetypes throughout classical literature, film, and art. Hosted by two teenagers
Project director, Kelly Campbellm
Host : Jason, Dianne
DVD Format
Keywords: Mythology in literature; Classical literature; Mythology, Classical; Roman mythology; Greek mythology